The Impact of Funding Risk on the Stability of Islamic Rural Banks in Indonesia - Dyah Widhowaty Eko Purnomo Putri; Hanim Hj Misbah (Master of Economics, Department of Economics, Faculty of Business and Economics, Universitas Islam Indonesia, 2026)
Non-Indexed Publication